2019
DOI: 10.3390/healthcare7020068
|View full text |Cite
|
Sign up to set email alerts
|

Living Alone Among Older Adults in Canada and the U.S.

Abstract: Increasing proportions of people, including older adults, live alone. Studying living arrangements of the elderly is important because these affect and reflect general well-being of the elderly and inform communities’ response to elderly housing needs. We analyze data from the 2006 Canadian Census and the 2006 American Community Survey to examine living alone among non-married older adults aged 55 and older in Canada and the U.S. The paper has two parts. First, we compare native- and foreign-born elderly to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
(56 reference statements)
0
28
0
1
Order By: Relevance
“…Moreover, elders are also considered a high risk group for COVID-19 infections ( Nicola et al, 2020 ). Compared to western countries, the prevalence of elders living alone in developing countries is very low ( Lee & Edmonston, 2019 ; Sundström et al, 2009 ). Although a trend in increase number of nuclear elders is developing, in a national survey, it was found that only 2% Indian elders live alone and 9% live with their spouse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elders are also considered a high risk group for COVID-19 infections ( Nicola et al, 2020 ). Compared to western countries, the prevalence of elders living alone in developing countries is very low ( Lee & Edmonston, 2019 ; Sundström et al, 2009 ). Although a trend in increase number of nuclear elders is developing, in a national survey, it was found that only 2% Indian elders live alone and 9% live with their spouse.…”
Section: Introductionmentioning
confidence: 99%
“…This is a signi cantly higher percentage of older adults expecting to live independently in China compared with older people in general. For instance, a comprehensive report on living arrangements of older adults showed that more than 70% older people in less developed countries co-resided with children [30]. Based on the responses to our questionnaires, we observed that the primary reason for older adults living alone was to avoid bothering their children, while secondary reasons were not having a child or their child was unable to provide care.…”
Section: Anticipated Living Arrangements and In Uencing Factorsmentioning
confidence: 79%
“…This special issue of Healthcare on "Creating Age-Friendly Communities: Housing and Technology" is timely, comprising twelve papers [16][17][18][19][20][21][22][23][24][25][26][27] that traverse and intersect across the fields of gerontology, health and social care, social sciences and gerontechnology.…”
mentioning
confidence: 99%
“…Recommendations were proposed as a way of improving the lives and social connectedness of older citizens, while for many participants living in rural locations, the use of technology such as Skype was greater for maintaining a connection with children and grandchildren living across the country or on a different continent. Lee and colleagues [22] explore in their body of work "Living Alone Among Older Adults in Canada and the U.S.", Canadian and American data sets to understand the living arrangements of older adults and how one's living arrangement can affect wellbeing, whilst informing respective housing needs. In a second part of the data analysis, they explore the various factors of immigrants who live alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation